PEMBERIAN LEAFLEAT KAWASAN EKOWISATA SEBAGAI SARANA INFORMASI BAGI PENGUNJUNG DI DESA TIWINGAN BARU, KABUPATEN BANJAR - Farah Qubayla; Setia Budhi; Ahmad Riswan; Rizqi Amalia; Sri Maulida Juniarti; Aulia Rahmi; Muhammad Azkia Yasma Kausha; Shella Aryanti; Muhammad Faqih Runadi (Wadah Inovasi Indonesia, 2022)
The purpose to be achieved from this community service activity is to develop ecotourism based on regional autonomy, Desa Tiwingan Baru, Kecamatan Aranio, Kabupaten Banjar. Problems encountered in efforts to establish ecotourism areas are; there is not information media as a means of supporting and developing tourism that comes and developing ecotourism areas based on regional spatial planning, Ecotourism institutions that are not conducive and cultural conditions of the community that tend to be subsystems. The methodology used in this activity is through focus group discussions, analysis of the supporting factors for the development of tourist attractions in Pulau Pinus and Bukit Batas. Things that have been done are (1) Strengthening existing tourist attractions and helping ecotourism person was very helped with tourist leaflets and location plans, creating social media accounts, and loading creative content (2) The activity has been achieved with desired purpose